CONSUMER SATISFACTION AND LOYALTY OF MODERN COFFEE SHOPS IN THE CITY OF MEDAN - Siregar, Naloan Saputra; Safitri, Sri Ariani; Dalimunthe, Apip Gunaldi (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2024)
This research aims to determine the consumer decision-making process in purchasing coffee at modern coffee shops and the level of consumer satisfaction and loyalty towards modern coffee shops in Medan Petisah District. The sampling technique used in this study is purposive sampling. Data analysis using descriptive analysis, CSI, IPA, and brand loyalty. Research results obtained: 1) In The process of purchasing Miel Coffee products, most consumers consider it important to drink coffee every day, then choose to drink coffee at Miel Coffee because of its attractive place and learn about Miel Coffee from friends with the initial consideration to visit due to the comfort of the place, then decide to buy spontaneously and feel satisfied after consuming coffee at Miel Coffee. 2) The level of consumer satisfaction with Miel Coffee's attributes is 82 percent, which means consumers are delighted with the service provided by Miel Coffee. Based on the Importance Performance Analysis (IPA) results, the attributes that need to be maintained are those in quadrant II. 3) The results of consumer loyalty at Miel Coffee are pretty good. Miel Coffee consumers can be considered quite loyal because most of them have recommended that others buy from Miel Coffee.